2013
DOI: 10.1111/gcb.12190
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of the calcifying larval stage of the Antarctic sea urchin Sterechinus neumayeri to near‐future ocean acidification and warming

Abstract: Stenothermal polar benthic marine invertebrates are highly sensitive to environmental perturbations but little is known about potential synergistic effects of concurrent ocean warming and acidification on development of their embryos and larvae. We examined the effects of these stressors on development to the calcifying larval stage in the Antarctic sea urchin Sterechinus neumayeri in embryos reared in present and future (2100+) ocean conditions from fertilization. Embryos were reared in 2 temperature (ambient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 82 publications
(152 reference statements)
5
60
0
Order By: Relevance
“…We analysed data on arm length prior to commencement of feeding because after food is introduced to sea urchin larval cultures, comparisons between studies are confounded by the natural phenotypic plasticity in arm growth due to a feedback mechanism linking nutritive rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120439 environment (food levels and larval density) and arm length, the expression of which differs among echinoid families [40,41]. Most studies report pH on the pH NIST (National Institute of Standards and Technology) scale, which is approximately 0.1 units lower than the pH t (total) scale ( [69], see also, [26,58]). To compare all data on the NIST scale, we added 0.1 pH units to the pH t values provided by studies that used this scale.…”
Section: Methodsmentioning
confidence: 99%
“…We analysed data on arm length prior to commencement of feeding because after food is introduced to sea urchin larval cultures, comparisons between studies are confounded by the natural phenotypic plasticity in arm growth due to a feedback mechanism linking nutritive rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120439 environment (food levels and larval density) and arm length, the expression of which differs among echinoid families [40,41]. Most studies report pH on the pH NIST (National Institute of Standards and Technology) scale, which is approximately 0.1 units lower than the pH t (total) scale ( [69], see also, [26,58]). To compare all data on the NIST scale, we added 0.1 pH units to the pH t values provided by studies that used this scale.…”
Section: Methodsmentioning
confidence: 99%
“…Such results suggest that in polar regions the effects of GCC may manifest in greater P CO2 variability. Potential biological effects of elevated P CO2 have already been observed in several laboratory studies on Antarctic calcifying marine organisms, including morphological changes with reduced growth (Yu et al, 2013), developmental malformations (Byrne et al, 2013) and the dissolution of shells (Orr et al, 2005;McClintock et al, 2009;Bednaršek et al, 2012). Physiological alterations in oxygen consumption rates, heat shock proteins and enzymes involved in shell growth have also been observed (Cummings et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…These studies have focused on the effect of a single stressor or a combination of temperature and pH on adult sea urchins, during fertilization and early developmental stages [53][54][55][56][57]. S. neumayeri has shown that under long term acclimation, adult stages are lest affected by two combined effect of temperature and reduced seawater pH [56].…”
Section: Discussionmentioning
confidence: 99%